Cystoscopy-assisted laparoscopy for bladder endometriosis: modified light-to-light technique for bladder preservation - Rafael Mamprin Stopiglia; Ubirajara Ferreira; Daniel Gustavo Faundes; Carlos Alberto Petta (International Brazilian Journal of Urology)
ABSTRACT Introduction Endometriosis is a disease with causes still unclear, affecting approximately 15% of women of reproductive age, and in 1%-2% of whom it may involve the urinary tract. The bladder is the organ most frequently affected by endometriosis, observed around 85% of the cases. In such cases, the most effective treatment is partial cystectomy, especially via videolaparoscopy. Study Objective, Design, Size and Duration In order to identify and delimit the extent of the intravesical endometriosis lesion, to determine the resection limits, as well as to perform an optimal reconstruction of the organ aiming for its maximum preservation, we performed a cystoscopy simultaneously with the surgery, employing a modified light-to-light technique in 25 consecutive patients, from September 2006 to May 2012. Setting Study performed at Campinas Medical Center – Campinas – Sao Paulo – Brazil.Participants/materials, setting and methods: Patients aged 27 to 47 (average age: 33.4 years) with deep endometriosis with total bladder involvement were selected for the study. The technique used was conventional laparoscopy with a transvaginal uterine manipulator and simultaneous cystoscopy (the light-to-light technique). A partial videolaparoscopic cystectomy was performed with cystoscopy-assisted vesical reconstruction throughout the entire surgical time. The lesions had an average size of 2.75cm (ranging from 1.5 to 5.5cm). The average surgical time was 137.7 minutes, ranging from 110 to 180 minutes. Main Results Postoperative follow-up time was 32.4 months (12-78 months), with clinical evaluation and a control cystoscopy performed every six months. No relapse was observed during the follow-up period. Conclusions A cystoscopy-assisted partial laparoscopic cystectomy with a modified light-to-light technique is a method that provides adequate identification of the lesion limits, intra or extravesically. It also allows a safe reconstruction of the organ aiming for its maximum preservation.